Parasitic zoonoses: Assessing risk to indigenous communities in the Araquari region, Santa Catarina (Research, Society and Development, 2026)
Zoonotic diseases represent a significant public health issue, affecting human populations across diverse socio-environmental contexts. However, socially vulnerable groups, such as Indigenous peoples, are especially exposed to the risks associated with these diseases. Close contact with animals, lack of basic sanitation, precarious housing conditions, and limited access to healthcare services contribute to the persistence and spread of zoonotic agents within these communities. In the state of Santa Catarina, approximately 21,000 residents self-identify as Indigenous. In the region of Araquari-SC, there are Guarani communities facing challenges related to the health of their companion animals. Given this context, the present study aimed to assess the occurrence of parasites with zoonotic potential in animals living within these Indigenous communities, correlating parasitological, sanitary, and environmental aspects. Coproparasitological analyses, dermatological examinations, and blood collection from animals were carried out, along with a systematic evaluation of environmental and sanitation conditions in the villages. Zoonotic helminths and ectoparasites were detected, including Ancylostoma sp., Toxocara canis, Dipylidium caninum, Dirofilaria immitis, Ctenocephalides felis, Tunga penetrans, Sarcoptes scabiei and Amblyomma ovale. Other parasites that affect animal health, such as Rhipicephalus sanguineus, Demodex canis, Trichuris sp., and Otodectis sp., were also identified, with varying frequencies among the communities. No dogs tested positive for Leishmania infantum. The findings reinforce the need for intersectoral public policies based on the One Health approach, promoting epidemiological surveillance, health education, and structural improvements aimed at protecting human, animal, and environmental health in Indigenous communities.